(untitled) (El-Wahat Journal for Research and Studies, 2017)
The Private Sector Is Alone Bear The Funding In Holding Abbott State Was Very Beneficiaries In The Legislation Of Such Contracts Modern Of Benefits To Alleviate The Financial Burden On The State. Where The Holding Of Abbott Is A Contract Whereby The State To Award A Concession Of One Of The Persons Of The Private Sector To Undertake The Construction And Operation Of The Ownership Of The Annex For A Specified Period Of Time, After The End Of The Period Specified In The Contract Be Returned The Ownership Of The Facility Of The State. Which Type Of Participation Of The Private Sector And The Public Sector It Is Also Of Recent Decades As They Moved To The State; In Response To The Needs Of The Citizens Of The Public Utilities, .The Convening Under BOT Contract With An International Character Despite The Juristic Disagreement On The Nature Is The Holding Of A Civilian Or A Special Nature. It Inevitably Of An Administrative Contract; It Is Linked To The Annex, It Is One Of The Types Of Contracts Where It Is Considered Among The Concession Contracts Annex Of The Yea Key Words - Bot - Private Sector - Franchise Contract